ANALYSIS OF INFLUENCING OF THE GEOLOGICAL ENVIRONMENT FEATURES ON THE MAIN GAS PIPELINES USING DATA OF THE MULTISPECTRAL AEROSPACE SURVEY - ARISTOV, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The article is devoted to a character aspects of influencing of geologic environment on gas pipelines. Moistening of soils and corrosion-dangerous sites, the influencing of processes of endogenous and exogenous geodynamics on gas pipelines was studied in various geographic conditions applying the data of aerial and space remote sensing. The relevant decoding features of adverse processes on aerial and space images as well as features of applying the imaging in visible and infra-red bands for analysis of grounds along the pipelines' tracks are investigated.